Multiple brain infarctions and aneurysm of interatrial septum: Case report - M, Saravi (Babol University of Medical Sciences, 2004)
Background and Objective: Previous reports have described an association between atrial septal aneurysm and cerebral embolic events. We report this patient for clinical presentation of multi-infarction and role of transesophageal echocardiography in diagnosis of this condition. Case: A 40-year-old man was admitted in hospital because of sudden right hemiparesis, which repeated after three weeks with Wernicke dysphasia and after that degrees of apathy. Brain CT scan revealed some hypodense areas. Ultrasound study failed detect any thrombosis or stenosis in carotid, vertebral and basilar arteries. MRI was in favor of vascular events. No arrhythmia was found in holter ECG. Transthoracic and transesophageal echocardiography were in favor of atrial septal aneurysm without patent foramen ovale or any thrombus. Warfarin was started and there was no recurrence during follow up. Conclusion: Inter-atrial septal aneurysm is probably an important factor for stroke. Embolic event is due to migration of in situ thrombosis or transition through it. Marked mobility and thickness of aneurysm may also increase the risk of embolization. Transesophageal echocardiography is a helpful tool in the diagnosis and management of patients with stroke and this anomaly.